Reliability and validity of the Brazilian version of the Hospital Survey on Patient Safety Culture (HSOPSC): a pilot study - Reis, Cláudia Tartaglia; Laguardia, Josué; Vasconcelos, Ana Glória Godoi; Martins, Mônica (Cadernos de saúde pública, 2016)
The evaluation of the culture of patient safety in hospitals is nowadays considered as a management too, since it helps to identify problem areas and provide valuable information for planning improvements. This study explored the reliability and validity of the Brazilian version of the Hospital Survey on Patient Safety Culture, an instrument that evaluates characteristics of patient safety culture among hospital staff. The reliability of the instrument was evaluated by analyzing the internal consistency of each dimension. The validity of the tool was carried out by means of exploratory and confirmatory factor analysis. The sample was made up of 322 questionnaires that were collected in two Brazilian hospitals in 2012. Cronbach's alpha ranged from 0.52 to 0.91 for the different dimensions, with the exception of two, for which it was much lower. After excluding four items, the exploratory factor analysis presented adjusted indices that were appropriate for a 10 factor model. Resumen: La evaluación de la cultura de seguridad del paciente en el ambiente hospitalario se considera hoy una herramienta de gestión, pues permite identificar áreas problemáticas y proporciona información valiosa para la planificación de mejoras. Este estudio examinó la confiabilidad y la validez de la versión brasileña de la Investigación sobre Cultura de Seguridad del Paciente en Hospitales (HSOPSC), instrumento que evalúa características de la cultura de seguridad del paciente entre trabajadores de hospitales. La confiabilidad del instrumento fue evaluada a través del análisis de la consistencia interna de sus dimensiones. La validez del constructo se realizó mediante un análisis factorial exploratorio y confirmatorio. La muestra estuvo compuesta por 322 cuestionarios, recogidos en dos hospitales en Brasil, en 2012. Entre las dimensiones, el alfa de Cronbach varió entre 0,52 a 0,91, excepto para dos dimensiones en la que fue muy bajo. Tras la exclusión de 4 ítems, el análisis factorial exploratorio presentó índices de ajuste apropiados para un modelo de 10 factores. Resumo: A avaliação da cultura de segurança do paciente no ambiente hospitalar é hoje considerada uma ferramenta de gestão, pois permite identificar áreas problemáticas e fornece informações valiosas para o planejamento de melhorias. Este estudo examinou a confiabilidade e a validade da versão brasileira da Pesquisa sobre Cultura de Segurança do Paciente em Hospitais (HSOPSC), instrumento que avalia características da cultura de segurança do paciente entre trabalhadores de hospitais. A confiabilidade do instrumento foi avaliada através da análise da consistência interna de suas dimensões. A validade de construto foi realizada por análise fatorial exploratória e confirmatória. A amostra foi composta por 322 questionários coletados em dois hospitais no Brasil, em 2012. Entre as dimensões, o alfa de Cronbach variou entre 0,52 a 0,91, exceto para duas dimensões em que ele foi muito baixo. Após exclusão de 4 itens, a Análise Fatorial Exploratória apresentou índices de ajuste apropriados a um modelo de 10 fatores.